Public employment services and employers: how important are networks with firms? - Stefanie Behncke; Markus Frölich; Michael Lechner (Institute for the Study of Labor (IZA), 2007)
This paper examines whether contacts between caseworkers in public employment offices and employers impact on the reemployment chances of the unemployed they counsel. This analysis is made possible through a large administrative dataset on unemployed combined with an extensive survey of caseworkers' characteristics and their strategies. This data was created for evaluating public employment services in Switzerland. We use econometric techniques from the treatment evaluation literature to identify causal effects of a more intense employer focus of the caseworkers. The estimation results indicate that caseworkers who maintain direct contacts to firms achieve higher reintegration rates.
Keywords: 330; Arbeitsvermittlung; Soziales Netzwerk; Arbeitsverwaltung; Privatwirtschaft; Berufliche Integration; New Public Management; Schätzung; Schweiz